IDULFITRI MARKETING - Agus Hasan Pura A (Bina Ekonomi, 2011)
Marketing of led fitr is a seasonal marketing. More  than 200 million people  in Indonesia  are moslem  and as a moslem  they have an obligation  to do fasting  in ramadhan month before the led fitr. Unfortunately, moslems in lndonesia have mixed the value of lslam with their tradition such as "mudik” becomes an important part of people tradition in celebrating led fitr. During the period of ramadhan, demands of products are very high therefore it creates an opportunity for the marketer to reach higher sales and bigger profit particularly for those who understand consumer behavior. All variables in marketing mix should be changed based on changes of consumer behavior during ramadhan and ied  fitr.